Toward a More Responsive and Responsible Bureaucracy: Incorporation of Gender Norm in the EU and Japanese Staffing Policy - Fukuda, Tomohiro (Policy & Governance Review, 2025)
This paper discusses limited responsiveness of the public organizations to contemporary social norms. Bureaucracy is sometimes said to be slow and inadequate to accept new principles, but most preceding studies did not directly analyze its causes. This study takes the cases of the European Union and Japan and analyzes the intra and extra organizational impediments in the process of internalization of the gender norms into these personnel administration and draws a hypothesis of the cause(s) of bureaucratic limited responsiveness toward contemporary social norms by the method of agreement. In both cases, gender-related provisions existed in their regulation on staffing from its early days, but its effectiveness was enhanced only recently. In case of the EU before 2000, those responsible for the staffing were initially hesitant to incorporate gender criteria into its policy, and even after recognizing the importance of the norm, they had little idea on how to realize it. In case of Japan, effectiveness of legislation regarding gender equality has been incremental, which represented the practitioners' struggle on conflicting considerations on staffing. Through this analysis, the paper draws a conclusion that public organizations have developed and maintained its basic principles to strengthen its legitimacy and autonomy against its political control, but this bureaucratic practice paradoxically makes the organization less sensitive to newly emerged social norms.